Path Dependence, Lock-in, and Breakthrough: An Exploration of the Evolutionary Path and Evolutionary Mechanisms of Agricultural Industry Clusters: A Case Study of the Flower and Plant Industry Cluster of Jiangdu District in Yangzhou City, Jiangsu Province - Xu Jufen; Yang Yahan (Redai dili)
Owing to their low technological relevance and high dependence on policies, agricultural industry clusters are more likely to fall into inefficient locking-ins in the process of evolutionary development. Based on the perspective of evolutionary economic geography, this study analyzes the formation of path dependence and the locking-in and breakthrough of agricultural industrial clusters, and summarizes the main characteristics of industrial clusters in the dynamic evolution process. First, the study examines the three major elements of market, technology and institution, and presents an evolutionary analysis framework of agricultural industrial clusters from path selection, path reinforcement to path locking and path breakthrough. Second, it combines field research and semi-structured interviews to conduct qualitative research on the flower and plant industries in Jiangdu District, Yangzhou City. The evolution of this industry could be divided into four stages: industrial agglomeration in the initial period, cluster development in the expansion period, inefficient locking in the bottleneck period, and the creation of new paths in the transition period. Third, the research analyzes the evolutionary mechanisms of agricultural clusters. The results show that market demand is the fundamental driving force for the evolution of agricultural clusters, and the process could be regarded as a cycle of "demand feedback-supply adjustment-demand re-feedback" based on the basic principle of "market supply and demand matching." Furthermore, institutional support is a basic guarantee of the evolution of agricultural clusters. The creation of a new path requires innovative institutional supply, while adjusting the old path requires an appropriate policy to guide the exit of inefficient industries. Additionally, knowledge innovation is the key driving force for the evolution of agricultural clusters, including the exchange of experience based on geographical ties, the exchange of scientific knowledge and technology with greater professional depth, and the construction of more diversified knowledge networks in the mobile-Internet era. They contributed significantly to the self-reinforcement of industrial clusters. Above all, it is identified that the life cycle of the industry cluster theory continues to have explanatory power for the evolution process and mechanism of agricultural industry clusters. The three interrelated elements of market demand, institutional support, and knowledge innovation promote cluster evolution. When it meets market demand and exhibits growth, support measures such as space guarantees, infrastructure, communication activities, and industry organization tend to follow the trend, and the cluster is pushed forward to deeper levels of the industrial chain and knowledge network. When there is a structural mismatch between market supply and demand, limited resources (including land, capital, policy, and manpower) may be gradually withdrawn and turned to industries with greater growth potential. If there are no new growth opportunities or market demands, industrial clusters are likely to enter the trap of inefficient development or even disintegration. When the new format of the industry meets market demand again, industrial metamorphosis will occur in the new knowledge network, which will also lead to a more accurate institutional supply and a breakthrough from the old path.